2016
DOI: 10.1038/srep37245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high-titer lactic acid fermentation from NaOH- and NH3-H2O2-pretreated corncob by Bacillus coagulans using simultaneous saccharification and fermentation

Abstract: Lignocellulose is one of the most abundant renewable feedstocks that has attracted considerable attention as a substrate for biofuel and biochemical production. One such biochemical product, lactic acid, is an important fermentation product because of its great potential for the production of biodegradable and biocompatible polylactic acid. High-titer lactic acid production from lignocellulosic materials has been achieved recently; however, it requires biodetoxification or results in large amounts of waste was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…In addition to phenolic inhibitors, formate and acetate, which act as fermentation inhibitors, are also generated by alkaline pretreatment of a lignocellulosic biomass [ 9 ]. The growth of K. huakuii LAM0618 T and degradation of formate and acetate were tested in YPD medium (pH 6.0) containing different concentrations (2.0, 4.0, 6.0, and 8.0 g/L) of these inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to phenolic inhibitors, formate and acetate, which act as fermentation inhibitors, are also generated by alkaline pretreatment of a lignocellulosic biomass [ 9 ]. The growth of K. huakuii LAM0618 T and degradation of formate and acetate were tested in YPD medium (pH 6.0) containing different concentrations (2.0, 4.0, 6.0, and 8.0 g/L) of these inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Dilute acid, dilute alkaline, and alkaline peroxide pretreatments were compared, with wheat straw and corncob as substrates. These comparisons revealed that the alkaline peroxide pretreatment is the most appropriate method for ethanol and lactic acid production even without rinsing of the pretreated substrates [ 8 , 9 ]. In addition, the alkaline peroxide pretreatment retained more of the hemicellulose than during other pretreatments, and dissolved a portion of the lignin, promoting enzymatic hydrolysis and reducing the inhibitory effect of lignin derivatives on subsequent fermentation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corncob (LianFeng Processing of Agricultural Products Co. Ltd, Lianyungang, China) was cleaned, dried, and sieved using a 0.15 mm mesh. The corncob was then pretreated using the NH 3 ‐H 2 O 2 system, as we reported previously . Briefly, 1000 g of corn stover was pretreated with 3% NH 3 ·H 2 O for 2 days, and then pretreated with 5% H 2 O 2 for 7 days at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Several pretreatment techniques have been studied to improve the conversion of lignocellulosic materials into sustainable fuels, value-added chemicals and functional materials (Rajan and Carrier, 2014;Zhang et al, 2016;Qi et al, 2017). Pretreatment normally enhances substrate accessibility by breaking down the hemicellulose and/or lignin interface and expose the cellulose matrix to the concerted action of cellulolytic enzymes (Mood et al, 2013).…”
Section: Introductionmentioning
confidence: 99%